Observations and modelling of ion cyclotron emission observed in JET plasmas using a sub-harmonic arc detection system during ion cyclotron resonance heating. (10th July 2018) - McClements, K.G.; Brisset, A.; Chapman, B.; Chapman, S.C.; Dendy, R.O.; Jacquet, P.; Kiptily, V.G.; Mantsinen, M.; Reman, B.C.G.
Abstract: Measurements are reported of electromagnetic emission close to the cyclotron frequency of energetic ions in JET plasmas heated by waves in the ion cylotron range of frequencies (ICRF). Hydrogen was the majority ion species in all of these plasmas. The measurements were obtained using a sub-harmonic arc detection system in the transmission lines of one of the ICRF antennas. The measured ion cyclotron emission spectra were strongly filtered by the antenna system, and typically contained sub-structure, consisting of sets of peaks with a separation of a few kHz, suggesting the excitation of compressional Alfvén eigenmodes closely spaced in frequency. In most cases the energetic ions can be clearly identified as ICRF wave-accelerated 3 He minority ions, although in two pulses the emission may have been produced by energetic 4 He ions, originating from third harmonic ICRF wave acceleration. It is proposed that the emission close to the 3 He cyclotron frequency was produced by energetic ions of this species undergoing drift orbit excursions to the outer midplane plasma edge. Particle-in-cell and hybrid (kinetic ion, fluid electron) simulations using plasma parameters corresponding to edge plasma conditions in these JET pulses, and energetic particle parameters inferred from the cyclotron resonance location, indicate strong excitation of waves at multiple 3 He cyclotron harmonics, including the fundamental, which is identified with the observed emission. These results underline the potential importance of ICE measurements as a method of studying confined fast particles that are strongly suprathermal but have insufficient energies or are not present in sufficient numbers to excite detectable levels of γ -ray emission or other collective instabilities.